Ameliorative Effects of Stem bark Extract of Pterocarpus erinaceus on Indomethacin-induced Ulcer - Umaru, Isaac John; Olawale, Otitoju; Okoli, Emmanuel Chikodiri; Tensaba, Akafa Andes; Umaru, Kerenhappuch Isaac; Istifanus, Dafup Kadel; Umahi, David (African Journal of Biochemistry and Molecular Biology Research, 2024)
Pterocarpus erinaceus serve as a medicinal plant to many populations of Nigeria and West Africa. The stem bark, leaves, and root bark have been studied for their antioxidant, antimalaria, antiulcerogenic, and antibacterial properties. The study examined the anti-ulcerogenic properties of Pterocarpus erinaceus stem bark extracts in albino rats with indomethacin-induced ulcers and hepatic biochemical changes. The anti-ulcer effect was determined by histopathological examination of ulcerated rats treated with the stem bark extracts in a period of 14-days. The three extracts did not cause elevation of key liver biomarkers such as AST, ALT, and ALP. Hence are considered not non-toxic at the dose and duration given. The leaf extract exhibited anti-ulcer effect at 100, 200, and 300 mg/kg.